2016
DOI: 10.1242/dev.135285
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeling enzyme Snf2h regulates embryonic lens differentiation and denucleation

Abstract: Ocular lens morphogenesis is a model for investigating mechanisms of cellular differentiation, spatial and temporal gene expression control, and chromatin regulation. Brg1 (Smarca4) and Snf2h (Smarca5) are catalytic subunits of distinct ATP-dependent chromatin remodeling complexes implicated in transcriptional regulation. Previous studies have shown that Brg1 regulates both lens fiber cell differentiation and organized degradation of their nuclei (denucleation). Here, we employed a conditional Snf2h flox mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 88 publications
1
32
0
Order By: Relevance
“…In addition, luciferase assays revealed that the DNaseIIβ promoter is modulated by N-myc in lens-derived cells. Interestingly, the expression of other transcriptional regulators of DNaseIIβ expression in the lens (Pax6, Hsf4, Brg1, Snf2h and Prox1) (Audette et al, 2016; He et al, 2016, 2010) was not altered in N-myc -deficient lenses (Figs. 5, 7 and S5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, luciferase assays revealed that the DNaseIIβ promoter is modulated by N-myc in lens-derived cells. Interestingly, the expression of other transcriptional regulators of DNaseIIβ expression in the lens (Pax6, Hsf4, Brg1, Snf2h and Prox1) (Audette et al, 2016; He et al, 2016, 2010) was not altered in N-myc -deficient lenses (Figs. 5, 7 and S5).…”
Section: Discussionmentioning
confidence: 99%
“…4 × 10 3 cells/well were plated (96-well plate) and cultured for 40 h. Using Lipofectamine 3000, pUB, pUB-N-myc, pkw10 or pwk10-Pax6 plasmids were co-transfected with 100 ng DNaseIIβ-luc (He et al, 2016) and 10 ng CMV- Renilla (Promega). Thirty hours after transfection Firefly and Renilla luciferase activity were measured using Dual luciferase reporter assay system (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Loss of the ATP‐dependent chromatin remodelling enzyme Snf2h is vital for lens development in mice. Interestingly, depletion of Snf2h dramatically reduces HSF4 transcript levels, suggesting that the transcription factor is regulated by chromatin remodelling, and that the role of Snf2h in lens development might be in part mediated by HSF4 .…”
Section: Hsf Family Membersmentioning
confidence: 99%
“…During denucleation, the elongated "ovoid-like" lens fiber cell nuclei first change their shape into a more sphere-like structure, and with continuous chromatin condensation their size is gradually reduced, followed by abrupt disintegration of the nuclei into multiple apoptotic-like particles (30,31). Lens fiber cell denucleation can be blocked by mutations in a group of genes; for example, the ATP-dependent chromatin-remodeling enzyme Snf2h (Smarca5) is required for this process through regulation of transcription factor Hsf4 and its target the Dnase2b gene (32), which encodes a lysosomal enzyme that degrades lens nuclear DNA (33). In other systems, Snf2h regulates a variety of nuclear processes, including assembly and sliding of nucleosomes along the DNA strand, and has known functions as a positive or negative regulators in RNA polymerase II transcription (34 -37).…”
Section: Transcriptional Bursting During Lens Differentiationmentioning
confidence: 99%